INVENTORY OF ARTHROPODS ON SESBANIA ACUELATA IN THE ALGERIAN SAHARA AND QUANTIFICATION OF PHENOLIC COMPOUNDS BY HPLC - larkem, I.; Benchikha, N.; Domandji, S.; Domandji, M. B. (University of Eloued جامعة الوادي, 2017)
The present study was carried out at the I.T.D.A.S. (Biskra). It contributes to the inventory and knowledge of arthropods which are successfully infecting a plant newly introduced in Algeria in this case Sesbania acuelata. During the summer of 2016, each month, arthropods are collected using three methods: pitful traps, yellow water traps and direct hunting. The survey resulted in the retrieval of 685 individuals in 125 arthropods, grouped into 66 families and 13 orders. The results thus obtained showed a predominance of the order Hymenoptera followed by Diptera and Orthoptera. The Order of the acari is the least represented. For a better qualitative and quantitative analysis of the species identified, numerous ecological indices were used. Â Â Â The extract obtained was analyzed, under optimum conditions, by HPLC which allowed the identification of seven phenolic compounds which are ascorbic acid, gallic acid, chlorogenic acid, caffeic acid, and Vanillin, quercitin, rutin acids. Â Â Â Sesbania acuelata, can be, however, considered as a plant of pharmaceutical utility of great importance in addition to the other virtues.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Inventory, Arthropods, Sesbania acuelata, phÃ©nolic compounds, HPLC